Plasmid Profiles of Lactose-Negative and Proteinase-Deficient Mutants of Streptococcus lactis C10, ML(3), and M18 - Kuhl, Steve A. (1979)
Lactose- and proteinase-negative (Lac(−) Prt(−)) mutants of Streptococcus lactis C10, ML3, and M18 were isolated after treatment with ethidium bromide. The Lac(−) Prt(−) mutants of C10 were missing a 40-megadalton plasmid. A 33-megadalton plasmid was absent in the ML3 mutants, and the M18 variants lacked a 45-megadalton plasmid. The results suggest a linkage of these metabolic traits to the respective plasmids. The possible complexity of the interrelationship between lactose metabolism and proteinase activity is presented.